MXene/air-laid paper composite sensors for both tensile and torsional deformations detection. (June 2021) - Lin, Changhao; Luo, Shaohong; Meng, Fancheng; Xu, Bin; Long, Tao; Zhao, Yixin; Hu, Haibing; Zheng, Lianxi; Liao, Kin; Liu, Jiehua
Abstract: Two-dimensional Ti3 C2 Tx MXene nanosheets with excellent electrical conductivities have been synthesized in this work. The nanosheet is further assembled with air-laid paper and polydimethylsiloxane substrate, for sensing both tensile and torsional deformations. Results show that the sensor is able to detect a linear stretchability of up to 90% with the corresponding gauge factor of 1–2.58. After repeated stretching and releasing cycles at a strain of 10% for 2000 cycles, the remaining change of relative resistance is only 0.1. Particularly, the sensor also displays responsive electrical signal change when torqued from 0 to 2π radian, suggesting a potential application for torsion deformation detecting. For demonstration, the sensor is applied in real-time monitoring the physiological movements, revealing outstanding capability of recognizing motions of finger bending, squat/rise, speaking and twisting. Graphical abstract: Image 1 Highlights: A novel MXene-based flexible sensor is prepared by the self-assembly process. Both tensile and torsional deformation can be detected by the sensor. The sensor demonstrated high sensitivity and resolution in monitoring human motions.